War Crimes in the International Humanitarian Law - S. I. Krasov (Московский журнал международного права, 2008)
The institute of international criminal liability of individuals has undergone a long and complicated process of elaboration. Initially the efforts in this sphere were concentrated only in scientific works of international law scholars who found that war was an acceptable way of solving international disputes. The most important question in the doctrine of international criminal liability was the issue of personal liability of individuals who committed war crimes.In the article the author points out the tendencies and provides an indepth analysis of the history of elaboration of the institute of international criminal liability on the basis of numerous works of major scholars in this field starting with Hugo Grocius. Primarily the author focuses on the period of the XIX century and states that neither international legal acts nor international law doctrine of the period could not rise up to the fact of necessity of abolishing international war crimes and first of all of abolishing aggressive war. But without these efforts the active elaboration of the norms of international humanitarian law in the period between the world wars would not have been possible.